Parameters’ Identification of Perzyna and Chaboche Viscoplastic Models for Aluminum Alloy at Temperature of 120ºC - KŁOSOWSKI, Paweł; MLECZEK, Anna (Engineering Transactions, 2014)
The main purpose of this paper is the parameters identification of the Perzyna and the Chaboche models for the aluminum alloy at elevated temperature. The additional purpose is comparison of the results for these viscoplastic models. The results have been verified by the numerical simulation of the laboratory tests. The material parameters have been calculated on the basis of the uniaxial tension test. The determination of the Perzyna model’s parameters has been made on the basis of the ideas presented in papers of Perzyna ([14–16, 18]). Then the parameters identification of the Chaboche model has been performed using concept presented in [2, 5, 6]. The elastic and inelastic properties have been estimated using the non-linear approximation by the least-squares method in Marquardt–Levenberg variant [12, 13]. The correctness assessment of the performed approximation has been verified by correlation and determination coefficients.